Isoprostane in systemic sclerosis: A systematic review and meta-analysis. Issue 3 (4th May 2019) - Ames, Paul R. J.; Merashli, Mira; Bucci, Tommaso; Nourooz-Zadeh, Jaffar
Abstract: Objectives: To further the knowledge of oxidative stress in systemic sclerosis (SSc), we performed a systematic review and meta-analysis on studies measuring isoprostane, a vasoactive agent deriving from arachidonic acid and implicated in the vasculopathy of SSc. Methods: Systematic search following the PRISMA guidelines in PubMed and EMBASE between January-1990/December-2017 using the terms: oxidative stress, isoprostane, systemic sclerosis and scleroderma. Results: After the screening process, 8 studies including 240 SSc patients and 192 controls were included in the systematic review and meta-analysis, 6 investigating urinary and 2 serum isoprostane: random effect meta-analysis revealed isoprostane overgeneration in SSc ( p  < .001) with wide heterogeneity ( I 2  = 75%). Subgroup analysis on urinary isoprostane favoured excess excretion in SSc ( p  = .009) with slightly lower heterogeneity ( I 2  = 67%); further subgroup analysis according to unit of measurement revealed no increased isoprostane excretion when expressed as pg/mg creatinine but increased when expressed as pmol/mmol creatinine ( p  = .05) with medium heterogeneity ( I 2  = 32%). Subgroup analysis on serum isoprostane favoured overproduction in SSc ( p  < .0001) with no heterogeneity. Conclusion: There is some evidence for isoprostane overgeneration in SSc that confirms the occurrence of oxidative stress in this setting: further prospective studies with specified outcomes are needed to evaluate the prognostic value of this functional biomarker.